The Influence of Time Management and Teacher Commitment on Teacher Performance in Junior High Schools in Tualang District, Siak Regency - Mensupriantos, Mensupriantos; Chairilsyah, Daviq; Futra, Dedi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
Teacher performance is something that needs and deserves to be examined in depth. Many factors cause problems related to teacher performance. This article will discuss the influence of time management and teacher commitment on teacher performance at junior high schools in Tualang District, Siak Regency. This research uses a quantitative-descriptive approach. This quantitative descriptive research systematically, actually, and accurately describes certain social phenomena, with the aim of describing in detail the existing facts and data. Data collection techniques use observation, documentation, and questionnaires. The subjects of the research were 107 teachers in public middle schools in Tualang District, Siak Regency. The research results show that 1) time management has a significant positive influence on teacher performance, with a significance value of 0.000 or less than an alpha value of 0.05. 2) Teacher commitment has a significant positive influence on teacher performance, with a significance value of 0.000. 3) Time management and teacher commitment jointly influence teacher performance, with a significance value of 0.000 and an R-Square value of 0.569, indicating that the proportion of influence of time management variables and teacher commitment on teacher performance variables is 56.9%.